ABHD5 as a friend or an enemy in cancer biology? - Cai, Jianya; Cheng, Hongwei; Xu, Shuangta (Frontiers in Oncology, 2024)
Alpha beta hydrolase domain containing 5 (ABHD5) is an essential coactivator of adipose triglyceride lipase (ATGL), a rate-limiting enzyme in various cell types that promotes the hydrolysis of triacylglycerol (TG) into diacylglycerol (DG) and fatty acid (FA). It acts as a critical regulatory factor in cellular lipid metabolism. The reprogramming of lipid metabolism is one of the hallmarks of cancer, suggesting that altering lipid metabolism could become a new strategy for tumor treatment. Research has revealed a close association between ABHD5 and the development and progression of malignancies. This review summarizes the role of ABHD5 in various malignant tumors and explores the different signaling pathways and metabolic routes that may be involved, providing a comprehensive mechanistic understanding of ABHD5.